2018
DOI: 10.1016/j.jid.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Peeling Skin Disorders: A Paradigm for Skin Desquamation

Abstract: Epidermal desquamation is the highly regulated process of invisible shedding of corneocytes from the outermost layers of the stratum corneum. This occurs through the interplay between proteases and their inhibitors that control the degradation of corneodesmosomes. Skin peeling refers to exaggerated visible superficial desquamation and can occur in inherited and acquired conditions. The illumination of the molecular basis of genetic disorders with skin peeling sheds light on the biological mechanisms of epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Yet, if is true then, in general, all absorbed dietary protein is only utilized for EE ; and thus, over time, total body protein persistently decreases because the EE -independent protein loss is not being compensated by dietary intake. EE -independent protein loss occurs in feces (e.g., excretion of mucin, an indigestible protein secreted by the intestinal mucosa [ 27 ]), in sweat (e.g., amino acids may be excreted during physical exertion [ 28 ]), in urine (e.g., urinary excretion of glycine in creatinine [ 29 ] and C-peptide [ 30 ], a 31 amino acid polypeptide generated from insulin secretion) and during renewal of skin, hair and nails (e.g., shedding of dead cells filled with keratin [ 31 , 32 , 33 ]). As a consequence, we run into a contradiction since body weight is simultaneously stable (true absorbed-oxidation identities imply mass balance) and decreasing (body protein is continuously diminishing).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Yet, if is true then, in general, all absorbed dietary protein is only utilized for EE ; and thus, over time, total body protein persistently decreases because the EE -independent protein loss is not being compensated by dietary intake. EE -independent protein loss occurs in feces (e.g., excretion of mucin, an indigestible protein secreted by the intestinal mucosa [ 27 ]), in sweat (e.g., amino acids may be excreted during physical exertion [ 28 ]), in urine (e.g., urinary excretion of glycine in creatinine [ 29 ] and C-peptide [ 30 ], a 31 amino acid polypeptide generated from insulin secretion) and during renewal of skin, hair and nails (e.g., shedding of dead cells filled with keratin [ 31 , 32 , 33 ]). As a consequence, we run into a contradiction since body weight is simultaneously stable (true absorbed-oxidation identities imply mass balance) and decreasing (body protein is continuously diminishing).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Defects in corneodesmosome components themselves have been involved in corneodesmosome abnormality and lead to epidermal barrier impairment as follows: Abnormalities in genes encoding corneodesmosin can cause a generalized inflammatory type of peeling skin syndrome and those encoding desmoglein 1 can induce another generalized inflammatory type of peeling skin syndrome, SAM syndrome (severe skin dermatitis, multiple allergies, and metabolic wasting) [56,57].…”
Section: Desquamationmentioning
confidence: 99%
“…One of the well-known examples is the severe autosomal recessive form of ichthyosis, Netherton syndrome, caused by a defect in the serine-specific inhibitor Kazal type 5 (SPINK5) gene encoding LEKTI. Netherton syndrome has also been proposed as a generalized inflammatory type of peeling skin syndrome [56]. Lack of serine protease inhibition can increase activities of KLKs, thereby causing acceleration in the degradation of the corneodesmosome [57,58].…”
Section: Desquamationmentioning
confidence: 99%
“…Despite differences in the susceptibility to infectious and inherited diseases of epithelial surfaces, such as staphylococcal scalded skin syndrome (Handler and Schwartz, 2014) and Netherthon syndrome (Proksch et al, 2008), external and internal integumentary epithelia share some aspects of gene expression. These aspects include induction of genes in the epidermal differentiation complex and genes encoding intercellular connections that point to common, yet so far incompletely characterized mechanisms of barrier function (Bragulla and Homberger, 2009;Has, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Knockout studies of CDSN in mice showed a diminished integrity of corneodesmosomes leading to a detachment of the stratum corneum from the granular layers and lethal epidermal barrier defects in adult animals (Leclerc et al, 2009). In humans, loss-of-function mutations of CDSN result in severe skin barrier defects (Leclerc et al, 2009) and are causative for the peeling skin syndrome (Has, 2018).…”
Section: Introductionmentioning
confidence: 99%